Sine Qua Nons of Advertising Strategy in the Context of Indian Culture and Social Life: Exploring the Impact of Advertising on Indian Culture and Consumer Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Simply put, advertising is an important marketing strategy that works in conjunction withinformation and persuasion channels. Every single person is exposed to commercials on a daily basis.They've become an inseparable part of the print medium, whether it's newspapers or magazines, overtime. This is also true in the case of broadcast media, where ad-commercials predominate. The Indianadvertising industry has grown tremendously from a small business to a full-fledged industry. Thepurpose of this study is to determine the advertising attractions and the influence they have on Indianculture. Advertisements in India are not only used to sell products. It sells dreams, visions, and the idealway of life, while also reinforcing stereotyped values. The longer an individual is exposed to anadvertisement, the more likely it is that it will affect them. The appeals' goal is to change how peoplethink about themselves and how they decide whether or not to buy certain things will benefit them.Because India has such a large population and cultural diversity, the advertising industry has created awide range of advertisements to capture people's attention and persuade them to buy products. Theappeals are written in such a way that they have an impact on people's purchasing decisions.